2015
DOI: 10.1097/md.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyles Associated With Human Semen Quality

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 61 publications
2
50
0
Order By: Relevance
“…A total of 666 eligible subjects attended the followed-up procedure in 2014, among which 10 failed to provide semen sample. More detailed information about the study design, screening process and lifestyles questionnaire can be found in the previous report [20]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 666 eligible subjects attended the followed-up procedure in 2014, among which 10 failed to provide semen sample. More detailed information about the study design, screening process and lifestyles questionnaire can be found in the previous report [20]. …”
Section: Methodsmentioning
confidence: 99%
“…As described previously [20], the semen samples were collected in a special semen container via masturbation in a private room. Upon receipt, the semen appearance was recorded, and semen volume was measured by weighing, assuming 1 g of weight was equal to 1 ml of volume.…”
Section: Methodsmentioning
confidence: 99%
“…At first glance, we supposed this finding could be due to alcohol intake. For example, participants in the Chinese study drank less frequently and had higher sperm motility [25]. Nevertheless, the findings of a cross-sectional study of 8344 healthy men (in Europe and the USA) demonstrated that alcohol intake was not associated with motility no any other semen variable [26].…”
Section: Prace Oryginalnementioning
confidence: 90%
“…However, the median percentage of morphologically normal sperm was lower (8% vs. 14%). Although the prevalence of cigarette smoking was similar between our cohorts, the participants in the Chinese study drank alcohol less frequently (51% vs. 91%) [25].…”
Section: Prace Oryginalnementioning
confidence: 99%
See 1 more Smart Citation